الاستقرار النفسي وعلاقتھ بمستوى الطموح عند طلبة الجامعة - م.د. امل كاظم میره (College of Education for Women, 2019)
Education, who is dignified the community and transmit a stagnation to the movement and chaos into the system of the advancement and nettlesome to the production, so it is the human resource development focus of the overall development, as that man in general and university student in particular is a tool and purpose of development together, there is no development without human From this perspective the researcher felt there was a need to conduct a study to know the psychological stability among the students of the university and the detection level of ambition, the following specific question? What is the relationship between the psychological stability level with the ambition among the students of the university? The importance of the current research through the role of university students in community-building and progress forward, therefore, must maintain their mental health would like to be more ambitious in order to achieve the goals of the university and the community. ResearchObjectives: The objective of this research is to identify the psychological stability and level of ambition of the university students and to identify statistically significant differences in the psychological stability and level of ambition according to the gender variable, as well as to identify the correlation between emotional stability and the level of ambition. The research sample It is consisted of 200 students from the University of Baghdad and in the academic year (2010-2011), while the search tools have been preparing a measure of psychological stability by the researcher, and the adoption of a measure the level of ambition . The researcher used a number of statistical methods to analyze data from: 1 - test educational Administration 2 - Pearson correlation coefficient The results of the research showed the enjoyment of the research sample psychological stability and level of ambition, and the presence of statistically significant differences in psychological stability depending on the gender variable in favor of males. And there is no difference in the level of ambition according to the gender variable, and the results showed the presence of significant correlation between emotional stability and the level of ambition appeared above search a number of conclusions and recommendations and proposals.